Metode Fuzzy Tsukamoto untuk Menentukan Jumlah Produksi Teh Poci Mutiara - Purwanto, Agung; Limet, Octo Bian; Rijal, Saiful (LPPM UNIKA Santo Thomas, 2023)
Micro, Small-Medium Enterprises Teh Poci Mutiara is one of the businesses that processes tea and other drinks. The Small-Medium Enterprises of Teh Poci Mutiara process tea according to the amount of demand, but the number of requests that is uncertain every week makes it difficult for business actors to determine how much to produce. This study aims to predict the amount of teapot production in order to meet consumer demand. by using the Fuzzy Tsukamoto Method. The results of the research with the Fuzzy Tsukamoto Method obtained an accuracy of the production amount of 119 cups, this prediction aims to help businesses reduce losses and production costs.